Mutual authentication technique for detection of malicious nodes in wireless sensor networks - Singh, Inderpreet; Kumar, Rajan (International Journal of Engineering and Technology, 2018)
The wireless sensor network is the decentralized type of network in which sensor nodes can join or leave the network when they want. Due to self configuring nature of network security and energy, consumption is the major issue of the network. The Sybil is the denial of service type of attack in which sensor nodes can change its identification multiple times in the network. In this research work, mutual authentication technique is proposed which detect malicious nodes from the network which is responsible to trigger Sybil attack in the network. The simulation of proposed algorithm is performed in NS2 and results shows that proposed technique performs well in terms of energy and throughputÂ Â